2022
DOI: 10.1177/23259671221085577
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes After Hamstring ACL Reconstruction With Suture Tape Reinforcement in Adolescent Athletes

Abstract: Background: Previous studies have suggested that suture tape-reinforced anterior cruciate ligament (ACL) grafts may have higher ultimate failure loads without stress-shielding. In patients at high risk for graft failure, such as adolescents, the addition of suture tape could have beneficial outcomes. Hypothesis: Suture tape reinforcement (STR) of ACL grafts in adolescent patients would lead to fewer graft ruptures during early recovery, without hindering subjective outcomes. Study Design: Cohort study; Level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 35 publications
(64 reference statements)
1
21
1
Order By: Relevance
“…Critical application of the inclusion and exclusion criteria finally yielded nine studies ( Figure 2 ). One was a prospective cohort study (level 2) ( Shantanu et al, 2019 ), six were retrospective cohort studies (level 3) ( Bodendorfer et al, 2019 ; Parkes et al, 2021 ; Allom et al, 2022 ; Kitchen et al, 2022 ; Szakiel et al, 2022 ; von Essen et al, 2022 ), and two were case series (level 4) ( Lavender et al, 2021 ; Duong et al, 2022 ). All seven comparative studies were designed to compare patients who underwent ACLR with and without ST-augmented grafts ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Critical application of the inclusion and exclusion criteria finally yielded nine studies ( Figure 2 ). One was a prospective cohort study (level 2) ( Shantanu et al, 2019 ), six were retrospective cohort studies (level 3) ( Bodendorfer et al, 2019 ; Parkes et al, 2021 ; Allom et al, 2022 ; Kitchen et al, 2022 ; Szakiel et al, 2022 ; von Essen et al, 2022 ), and two were case series (level 4) ( Lavender et al, 2021 ; Duong et al, 2022 ). All seven comparative studies were designed to compare patients who underwent ACLR with and without ST-augmented grafts ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Six studies compared subjective scores between ACLR with or without STA at the final follow-up. The Tegner score used in two studies (Parkes et al, 2021;Kitchen et al, 2022) both yielded superior results in the augmentation group. Results of other scores were inconsistent across studies.…”
Section: Subjective Scoresmentioning
confidence: 99%
“…In a cohort study of 40 patients in each treatment group, Kitchen et al. 14 demonstrated significantly higher Tegner scores in patients with tape augmentation when compared to those without.…”
Section: Discussionmentioning
confidence: 98%
“…Further, this technique has demonstrated potential in improving both biomechanical 13 and clinical outcomes following ACL reconstruction. 14 Tape augmentation increases the strength of the graft complex, demonstrating greater load to failure and reduced elongation. 15 However, suture or tape augmentation techniques describe incorporating the suture or tape into a separate post from the ACL graft, such as with tibial anchors 16 or tibial suspensory devices.…”
Section: Introductionmentioning
confidence: 99%
“…2,3,17,23,50 In a scoping review including 6 biomechanical, 3 animal, 10 technical, and 3 clinical studies, Mackenzie et al 23 found that ACLR when augmented with suture tape as an internal brace significantly increased the strength of the graft complex and reduced graft elongation while maintaining equivalent complication rates as well as patient-reported outcomes (PROs) when compared with standard ACLR. Despite the promising results of previous studies that found IB to not only be safe 7,20,23,34,47 but also biomechanically superior to standard ACLR, 2,3,17,23,50,53 an unanswered question is whether ACLR with IB would translate clinically and lead to less graft retears or impact clinical outcomes and PROs.…”
mentioning
confidence: 96%